Error analysis in using gerunds and infinitives among English Education students at Universitas Negeri Padang - Sendra, Agung Rizqilla; Rani, Yati Aisya (Universitas Negeri Padang, 2025)
Grammar plays a crucial role in English learning as it helps students construct accurate sentences. Among various grammatical components, gerunds and infinitives are particularly challenging. A preliminary observation showed that 69.2% of students who had completed the Intermediate Grammar course considered these topics difficult to master. This research aims to analyze the types and dominant type of errors made by fifth-semester English Education students at Universitas Negeri Padang in using gerunds and infinitives. The study used a descriptive design with a translation test consisting of 24 items. Students’ answers were analyzed using Dulay et al.’s (1982) Surface Strategy Taxonomy, which includes omission, addition, misformation, and misordering. The analysis found 123 total errors. Misformation was the most dominant (89 errors or 72.35%), followed by omission (19 errors or 15.44%), misordering (11 errors or 8.94%), and addition (4 errors or 3.25%). These findings indicate that students still struggle to select the correct form between gerunds and infinitives, showing limited understanding of verb patterns and grammatical structures.